On p-Laplace Equations with Singular Nonlinearities and Critical Sobolev Exponent - Mohammed El Mokhtar ould El Mokhtar (Journal of Function Spaces)
In this paper, we deal with p-Laplace equations with singular nonlinearities and critical Sobolev exponent. By using the Nehari manifold, Mountain Pass theorem, and Maximum principle theorem, we prove the existence of at least four distinct nontrivial solutions.